The Role of Teacher Communication Skills During Implementation to Increase Student Success in Achieving Learning Outcomes - Rohayati; I. Rajaloa, Nani; Samsudin; Supit, Deisye; Tukiyo (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Teachers' interpersonal communication skills that affect students' academic achievement in the 21st century. The urgency of this research arises from the importance of the role of teachers in creating effective and meaningful learning experiences, especially in the era of globalization and rapid technological advances. The purpose of this study is to analyze how teachers' communication skills can improve students' motivation and engagement in the learning process. The research method used is quantitative with a survey approach. The study population consisted of high school students in Makassar City, with a sample of 674 students selected by simple random sampling. Data collection techniques were carried out through questionnaires designed to obtain information about student experiences and observations of teacher communication skills. Data analysis techniques used descriptive and inferential statistics to evaluate the relationship between communication skills and academic achievement. The results showed that good teacher communication skills significantly contributed to increased student motivation and achievement. These findings conclude that improving teacher communication skills needs to be considered to create a productive learning environment. The implication of this study is the need for training for teachers to develop interpersonal communication skills, so that they can improve students' overall learning experience.